Preliminary evaluation of the impact of a writing assessment system on teaching and learning (2008)
Motivated by the conviction that valid and reliable assessments can foster positive changes in instruction, we implemented a writing assessment system in the adult English program at the Language Center, EAFIT University, Medellín. To evaluate the impact of the system, we analyzed the improvement of 27 students’ writings over time. We also examined the quality of their teachers’ (n=35) teaching and assessment routines. Student progress was measured by looking at the syntactic complexity of the texts using an average number of words per T-unit. Teachers’ instructional practices were examined through portfolio analyses. Results show some improvement in students’ writings and that the teachers need to provide a better response to students by appropriately using the required assessment tools. Key words: Writing assessment, prompts, scoring rubrics, washback Con base en la creencia de que las evaluaciones válidas y confiables pueden motivar cambios positivos en la enseñanza y el aprendizaje, implementamos un sistema de evaluación para la escritura en el programa de inglés de un centro de idiomas en Colombia. Para evaluar el impacto del sistema, analizamos las mejoras de 27 escritos a través del tiempo. Igualmente se analizó la calidad de las prácticas de enseñanza y evaluación de 35 profesores. Las mejoras en los escritos se determinaron a través de la complejidad sintáctica usando como medida el promedio de número de palabras por texto entre unidades T. Las prácticas de evaluación y enseñanza se evaluaron mediante el análisis de portafolios de escritura. Los resultados indican ciertas mejoras en los escritos y la necesidad de proporcionar mayor entrenamiento y orientación para que los profesores utilicen el sistema de evaluación de manera más apropiada. Palabras clave: Evaluación de la escritura, instrucciones, rúbricas para calificar, efecto de arrastre